Pengembangan Modul Pembelajaran PAI Yang Menarik Dan Mudah Dipahami - Sri Gina Miranti; Yusra Ramadhana; Gusmaneli Gusmaneli (Pusat Riset dan Inovasi Nasional, 2024)
Developing PAI learning modules that are interesting and easy to understand is an important aspect in increasing the effectiveness of Islamic learning. In this context, the use of electronic modules and applications such as Flip PDF Professional can be an effective solution. Electronic modules enable the integration of various multimedia elements and formative quizzes, while Flip PDF Professional provides an attractive and interactive display with page flipping features and the addition of animated media. This second model facilitates independent learning that is more effective and enjoyable for students, in line with technological developments and modern educational needs. Therefore, the development of PAI learning modules must follow this digital trend to improve the quality of learning and student academic achievement.